SHARPENING CRITICAL ECONOMIC THINKING: INVESTIGATING THE IMPACT OF CASE-BASED LEARNING IN HIGHER EDUCATION - Imran, Ahmad Fadhil; Idham, Afif Zuhdy; Muhammad Yamin; Anto, Muhammad Ansar; Septiannisa Paramita (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Critical thinking in economics constitutes an essential competence for undergraduates to engage with the complexities of contemporary economic dynamics. Yet, conventional lecturer-centred approaches often constrain students from attaining such skills, particularly their capacity to connect theoretical constructs with real-world socio-economic challenges. This study seeks to reposition economics pedagogy by examining the impact of Case-Based Learning (CBL) on the development of critical economic thinking (CET). Employing a quasi-experimental design with non-equivalent control groups, the research involved 70 undergraduates in economics education at State University of Makassar, divided into experimental (CBL) and control (conventional) cohorts. Pre- and post-test assessments were administered using case-based instruments, and the data were subjected to validity and reliability checks, normality and homogeneity tests, and independent samples t-tests. The findings indicate that students exposed to CBL significantly outperformed their peers taught through traditional methods, particularly in applying theoretical concepts to authentic cases, engaging in evidence-based reasoning, and articulating the ethical and distributive implications of economic decisions. The study concludes that systematically embedding CBL into the economics curriculum is imperative for preparing graduates capable of navigating the complexities of contemporary economic realities.